Phytotoxicity risk assessment of diuron residues in sands on wheat, chickpea, and canola. - Win Win Pyone; Richard W Bell; Michael T Rose; Gavan McGrath (PLoS ONE)
While diuron residues are being detected more frequently in agricultural soils, there is limited information available regarding their potential phytotoxicity to non-target grain crops. This study aims to determine robust phytotoxicity thresholds for three common, but contrasting, crop species (canola, chickpea, and wheat) exposed to a range of diuron concentrations and to determine how loamy sand soil can change the toxicity thresholds relative to an inert sand. The log-logistic non-linear regression model proved most effective in determining toxicity thresholds by analysing crop responses to diuron. Canola was the most sensitive to diuron in sand followed by wheat and chickpea. Diuron exhibits higher phytotoxicity in sand compared to loamy sand, with ED50 values (which is the dose at which diuron causes a 50% decrease in plant growth) of 0.03 mg kg-1 and 0.07 mg kg-1 for canola shoot biomass inhibition and 0.01 mg kg-1 and 0.06 mg kg-1 for root dry weight reduction, respectively. The ED50 values for wheat shoot biomass (0.11 and 0.24 mg kg-1) in sand and loamy sand, respectively, and the ED50 values for root growth inhibition are 0.14 mg kg-1 in sand and 0.19 mg kg-1 in loamy sand. These values were lower than label concentrations and previously estimated average and maximum diuron residue loads (0.17 and 0.29 mg kg-1) in Western Australia paddocks. The larger ED50 values of diuron in the loamy sand can be attributed to higher soil organic matter and cation exchange capacity that decreased bio-available diuron levels. Average diuron residue loads in Western Australia crop fields exceed the ED50 value emphasizes the need for careful planning of crop rotations to avoid crop phytotoxicity from soil-borne diuron residues. Further study is needed to determine the effect of a wider range of soil properties such as pH, clay content, and soil organic matter on the phytotoxicity risk of diuron to rotational crops.